Nursing students' metaphors of first clinical experiences of encountering patients with mental disorders - Fatemeh Mansouri; Azar Darvishpour (BMC, 2024)
Abstract Background Psychiatric wards are one of the most stressful medical centers. Apprenticeship in mental health can cause feelings of stress and anxiety among nursing students. Investigating nursing students' beliefs about mental illnesses is very important to improve nursing education. The present study aimed to identify nursing students' metaphors for their first clinical experiences of encountering patients with mental disorders. Methods This descriptive qualitative study was conducted on 18 undergraduate nursing students studying in two nursing colleges at Guilan University of Medical Sciences, in the north of Iran, in 2022. The data were collected through semi-structured interviews and analyzed using Critical Metaphor Analysis by the MAXQDA 2007 software. Results The analysis of nursing students' metaphors led to the emergence of 36 metaphors and 5 categories. These categories were "experience of dealing with a mental patient is similar to fear mixed with excitement", " patient is similar to an errant human", " psychiatric hospital is similar to a prison", "nurse is similar to a prison guard", and "clinical instructor is similar to a supporter, sympathetic and knowledgeable friend". Conclusions The results showed their negative attitude towards the psychiatric hospital and health care providers. It is suggested that the findings of this study be taken into consideration in the planning of clinical education of nursing students.